2011
DOI: 10.1007/s00542-011-1322-y
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric property improvement of polymer-nanosized strontium titanate-composites for applications in microelectronics

Abstract: With respect to applications in microelectronics the frequency and temperature dependent dielectric properties of a series of polymer-based composites, consisting of a thermally curable unsaturated polyester-styrene resin and nanosized strontium titanate filler, have been characterized. Following earlier investigations targeting an improvement of dielectric properties the impact of a thermal treatment of the dielectric filler on the resulting composite properties was determined. In case of composites containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Compared with the reported ceramic/PVDF composites and conductive metal Zn/PVDF [5,7,9,20,21], the dielectric constant of PVDF/V 2 O 5 composites is significantly higher at low filler content. Furthermore, it can be obviously found that our V 2 O 5 /PVDF composites possess higher dielectric constant than other semiconductor/polymers nanocomposites, such as ZnO/PVDF, TiO 2 /polystyrene, and ZnO/ polyethylene reported at a low filler content [10,22,23].…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Compared with the reported ceramic/PVDF composites and conductive metal Zn/PVDF [5,7,9,20,21], the dielectric constant of PVDF/V 2 O 5 composites is significantly higher at low filler content. Furthermore, it can be obviously found that our V 2 O 5 /PVDF composites possess higher dielectric constant than other semiconductor/polymers nanocomposites, such as ZnO/PVDF, TiO 2 /polystyrene, and ZnO/ polyethylene reported at a low filler content [10,22,23].…”
mentioning
confidence: 93%
“…Thus, it is a key issue to enhance dielectric permittivity of polymers while retaining other excellent performances. One versatile route is to disperse a high dielectric constant ceramic powder [5,6] into the polymer matrix [7][8][9], which can combine excellent dielectric behavior of fillers with superior processing property and chemical stability from the polymers. However, the excellent dielectric properties of such composites need high particle concentration (over 60 vol%), which can lead to the degradation of mechanical properties and processability of the polymers.…”
mentioning
confidence: 99%
“…The pronounced permittivity increase passing 50°C can be attributed to the increasing polymer matrix flexibility approaching the glass transition temperature around 86°C. This effect was observed also for polyester-styrene based PMCs containing different barium and strontium titanates Hanemann et al 2011b). With respect to device fabrication and device stability a mismatch of the thermal expansion coefficients (Table 1) of the PCB, the electrodes and the dielectric layer has to be avoided.…”
Section: Pmc Characterizationmentioning
confidence: 74%
“…A thermal pretreatment of the ceramic at elevated temperatures caused a significant increase of the permittivity and a reduction of the loss factor Hanemann et al 2011a). Quite recently a similar permittivity enhancement was demonstrated in case of nanosized strontium titanate (Hanemann et al 2011b).…”
Section: Introductionmentioning
confidence: 92%
“…The polyamic acid (PAA) precursor was polymerized from ODA and PMDA in freshly distilled DMAC under stirring at room temperature for 24 h. Then, different amounts of PVDF powders (10,20,30,40, and 50 wt.%) were ultrasonically dispersed in DMAC for 1 h. In order to prepare homogeneous and different concentrations of PVDF/PAA solution, various weight fractions of PVDF/DMAC dispersion were added into the PAA solution with further vigorous stirring for 24 h. Then, the PAA was imidized using a standard thermal imidization method. Subsequently, the mixture was cast onto a piece of clean glass plate, and thermally imidized at 50, 100, 150, 200, and 250 °C for 1 h and 300 °C for 0.5 h to form PI/PVDF composite films.…”
Section: Preparation Of Pi/pvdf Compositesmentioning
confidence: 99%